Enhancing Mosque Financial Transparency through a Mobile System under ISAK 35 - Edy Anan; Zoniarti Zoniarti; Agung Wijanarko (Penerbit Goodwood, 2026)
Purpose: This study develops a mobile-based financial reporting system for mosques under ISAK 35 to improve the reporting quality and donor trust through real-time updates. Methodology/approach: Using the Rapid Application Development (RAD) method, this study covers system requirement analysis, design, implementation, and testing. Data were collected through observations, Focus Group Discussions (FGDs) with mosque administrators, and literature reviews. Usability was tested using black-box and task-based evaluations. Results: The system generates ISAK 35–compliant reports, including statements of financial position, comprehensive income, cash flow, and changes in net assets. This enables real-time recording and reporting, thereby improving transparency and efficiency. Usability testing showed that administrators found the system to be intuitive and useful, although some struggled with adjustment entries. The system also improves financial literacy and donor confidence. Conclusions: The ISAK 35–based mobile system strengthens mosque financial reporting and offers a practical and replicable model for nonprofit entities. Limitations: The system is limited by database capacity (200 MB, 500 rows), lacks integration with digital payment tools (e.g., QRIS), and does not fully support multi-user or multi-entity functions. Limited accounting knowledge among administrators also affects usage. Contributions: This study presents a digital financial management prototype that integrates ISAK 35 with mobile technology to build donor trust and improve responsible reporting. The model can be adapted for other nonprofits, such as churches, foundations, and NGOs.